Korelasi Antara Peran Guru Bimbingan dan Konseling Dengan Keterlambatan Siswa - Endang Fatmawati; Titin Swatinah; Suyono Suyono (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2021)
Discipline is the key to the success of the process of providing education in schools. Discipline can be put to goog use as an educational tool and material. As an educational tool, the function of discipline is to ensure the smoothness of the learning process which is the core of the educational process. Student delays are caused by several factors, namely personal factors that come from being lazy and undisciplined, family and environmental factors also greatly influence the purpose of this study to find out whether there is a correlation between the role of gukdance and counseling teachers and student delays at MTS Bustanul Ulum Kemiri Panti. The population in this study consisted of 200 students and the sample was chosen randomly. From the results of data analysis, it is known thay the results of statistical product moment testing the results obtained are 0.727, so when consulted with a rough interpretation table the amount is between 0.70 up to 0.90. Thus, it can be concluded that there is a correlation between the role of guidance and counseling teachers and student delays Keywords: guidance and counseling teachers; late behavior